Cultural Memory in Lithuanian Radio in 1926–1940 from a Quantitative Point of View - Krutulys, Titas (History / Istorija, 2025)
The article analyses the broadcasts of historical themes on Lithuanian radio from 1926 to 1940 using a quantitative content analysis method. It examines three radio stations: the State Radio, Klaipėda Radio, and Vilnius Radio stations. Archival sources and published radio programmes are used as the primary materials for studying them. This research aims to reveal the most characteristic themes of historical broadcasts found on the different radios, the most frequently mentioned historical periods, key personalities, and the nature of the broadcasts. The quantitative aspects are compared with data from the periodical press discussed in the historiography and the ideological principles of the nationalists who controlled the radio. Lithuanian radio was characterised by specific methods of disseminating cultural memory, which differed from other media of the time. The cultural memory conveyed was strongly influenced by the ideology of the nationalists.